Wave load effect analysis of a floating bridge in a fjord considering inhomogeneous wave conditions. (15th May 2018) - Cheng, Zhengshun; Gao, Zhen; Moan, Torgeir
Highlights: Wave load effects of a floating bridge in a fjord were analyzed. A method was proposed to account for inhomogeneous wave conditions. Inhomogeneous wave conditions were assumed based on field measurements and numerical simulations. The effect of inhomogeneity is found to differ for various response variables. Proper description of inhomogeneous wave filed is important. Abstract: When designing a floating bridge crossing a deep and wide fjord, a homogeneous wave field is usually assumed for simplicity. However, waves in fjords are commonly inhomogeneous, and hence the mentioned design practice introduces uncertainty, which should be assessed for the design. In this study, we proposed an approach to account for the inhomogeneous wave load effect on a floating bridge and applied it on a floating bridge that was initially proposed for crossing the Bjørnafjorden. The floating bridge considered is end-anchored, about 4600 m long and consists of a cable-stayed high bridge and a low bridge supported by 19 pontoons. Wave excitation loads on each pontoon were proposed to be modeled and applied separately to account for inhomogeneous waves. By considering 1-year and 100-year wave conditions, dynamic responses of the floating bridge subjected to homogeneous and inhomogeneous waves were analyzed and compared. It is found that inhomogeneous waves cause relatively larger sway motion, axial force, and strong axis bending moment, as well as significantly larger weak axis bending moment along the bridge girder than homogeneous waves. These responses depend on the inhomogeneity level of waves considered. Proper description of the wave field is therefore very important for evaluating the effect of inhomogeneous waves and associated uncertainties.